METHODOLOGY FOR ASSESSING STUDENTS’ PRAGMATIC SUCCESS IN FOREIGN LANGUAGE LEARNING - Rustamova Feruzabonu Ilkhomovna (NEW APPROACHES IN EDUCATION: PEDAGOGY, INNOVATION, AND DEVELOPMENT, 2026)
Abstract: Pragmatic competence has become an essential component of communicative competence in foreign language education, reflecting learners’ ability to use language appropriately in various social and cultural contexts. This article explores methodological approaches to assessing students’ pragmatic success, emphasizing both theoretical foundations and practical evaluation tools. It examines the challenges of measuring pragmatic performance, including context sensitivity, cultural variability, and subjective interpretation. The paper proposes a comprehensive assessment framework combining discourse completion tasks, role plays, self-assessment, and corpus-based analysis. The findings highlight the need for integrative, authentic, and contextually grounded assessment methods to ensure valid and reliable evaluation of learners’ pragmatic abilities.